Sociodemographic and clinical characteristics of people sickened by colorectal cancer undergoing surgical treatment (Research, Society and Development, 2020)
Objective: To analyze the sociodemographic and clinical characteristics of people with colorectal cancer who underwent surgical treatment at a referral hospital in the Brazilian Amazon. Methodology: A descriptive prospective study with a quantitative approach, using secondary data from the medical records of patients at a surgical clinic in a reference hospital in Pará. The study was conducted from October 2018 to April 2019, including inpatients who underwent surgical treatment of colorectal cancer. Results: information was collected from 33 medical records, with a prevalence of 19 male patients (57.5%), in 11 medical records the prevalent age was between 48 and 57 years old (33.3%), 29 browns (87.8%) , 21 married (63.6%), 11 with complete elementary school (33.3%), 18 referred from the emergency department (54.5%), with an average time of 11.1 months between the first symptoms and the start of surgical treatment, and the average of 12.2 days between admission and surgery. 11 (33.3%) patients underwent rectosigmoidectomy, 14 patients (27.4%) reported abdominal pain, 18 patients (54.5%) had a family history of cancer and 29 (87.8%) underwent ostomy. Conclusion: With these data, it is noticeable that colorectal cancer is a public health problem, in addition to having patient profile data that improve hospital planning and care. Lastly, it is important to encourage early diagnosis and screening for colorectal cancer as forms of timely treatment and prevention of the most severe stages of the disease.